The dynamics of diel growth of tomato and capsicum leaves with different lighting modes - Kolomiets, Oleg O.; Gloushen, Sergey V. (Experimental Biology and Biotechnology, 2019)
The diel growth of tomato and capsicum leaves under laboratory conditions was studied. Plant growth was monitored by DISP – digital image sequence processing method. Under round-the-clock lighting mode in both species was observed more or less permanent growth of leaves. When lighting mode of 12/12 h (day/night) was applied growth curves have changed dramatically. The maximum increment at a capsicum was registered at the beginning of night whereas at a tomato the maximum increment was observed for the second half of night and early morning. The obtained results show photoperiodism can play triggering role for inner circadian clock that control processes of cell proliferation and differentiation in leaves of plants.